One new and two known species of Dorylaimoidea (Nematoda) from West Bengal, India - Sen, Debabrata; Chatterjee, Amalendu; Manna, Buddhadeb (Zootaxa, 2012)
Small populations of Laimydorus istvani sp. n., Laimydorus baldus Baqri & Jana, 1982 and Dorylaimus sp. were collected fromthe soil around the roots of guava at south 24-Parganas district, West Bengal, India. Laimydorus istvani sp. n. is characterizedby its odontostyle being distinctly thicker than the cuticle at the same level, cardia shape: rounded-conoid, wide at pharyngo-intestinal junction, enveloped by intestinal tissue which forms a conical projection extending into the lumen of intestine;delicate ring-like structure between the pharyngeal base and the proper cardia. Laimydorus istvani sp. n. comes close to L.multialaeus (Khera, 1970) Baqri, 1985, L. siddiqii Baqri & Jana, 1982 and L. baldus Baqri & Jana, 1982, but can bedistinguished from these species on the basis of different morphometric measurements. The new species differs from L.multialaeus in having higher a value, lower b value and longer odontostyle in females, and. longer body, lateral guiding piecesand tail in males. From L. siddiqii the new species differs in having a shorter tail in relation to body length, shorter cardia withdifferent shape, shorter prerectum and longer rectum in female, different number of ventromedian supplements and shorterspicules in males. From L. baldus, it differs in having a longer body, greater a-value, longer odontostyle and odontophore andlonger tail in females. Laimydorus istvani sp. n. differs from the males of L. baldus by its longer body, greater c value and in thenumber of ventromedian supplements. The population of L. baldus from West Bengal agrees well with the original descriptionexcept for some variations in body, odontophore, prerectum and tail length. New data on male characters have been provided inthe present study. The specimens of Dorylaimus sp. come close to D. geraerti Baqri & Jana, 1986 except in some morphometricmeasurements including: b (4.2–5.1 vs. 4.3–4.7), odontophore length (33–54 μm vs. 40–43 μm, prerectum length in females(120–160 μm vs. 196–241 μm and tail length in females (247.5–294 μm vs. 249–406 μm). In males, the supplements (36 innumber) occur in a contiguous series (as is usually seen in the genus Dorylaimus Dujardin, 1845), whereas in the typespecimens of D. geraerti 35–38 supplements are largely contiguous except for a set of 4–5 spaced supplements in the middle of the series, showing a resemblance with the genus Ischiodorylaimus Andrássy, 1969.